Intracranial haemorrhage complicating infection in infant masquerading as non-accidental injury- a case series - Chng, Kay Ly; Mussadik, Umul Khairil Fatimah; Subramaniam, Kunasilan; Zainun, Khairul Anuar (Malaysian Society of Pathologists, 2022)
Introduction: The death of a ‘healthy’ child in a carer’s house is always suspicious until proven otherwise. There is a high burden of responsibilities for a Forensic Pathologist to analyse the case from different perspectives before reaching a reasonable conclusion. Case series: We report a case of acute Subdural Haemorrhage (SDH) complicating lung infection and a case of subarachnoid haemorrhage (SAH) complicating multi-organism infection with possible concomitant liver disease. Both the infants were brought-in-dead to the hospital from the carer’s house. There were no findings suggesting trauma. Conclusion: Acute Intracranial Haemorrhage (ICH) especially SDH has often been associated with inflicted head injury. Though the nontraumatic or “spontaneous” acute ICH is rare, it does exist due to multiple factors. Both the cases illustrated portrayed that the significance of the ICH has to be determined based on the autopsy findings as well as analysing the case holistically before arriving at the conclusion. Misdiagnosis of such uncommon complications could result in a catastrophic outcome.